Chemical Constituents of Tetra Pleura Tetraptera (Fabaceae) and their Antimicrobial Activities - Udobre, A. S.; Etim, E. I.; Udoh, A. E.; Johnson, E. C. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Tetrapleura tetraptera (Fabaceae) is a medicinal plant used traditionally in Nigeria to treat skin infection. It is also used in cooking soup and pepper soup for mothers of newly born babies to prevent post-partum contraction. This study dealt with the identification of five bioactive chemical constituents from the n-butanol Extract of the fruit of the plant. The extract contained some secondary metabolites and also demonstrated antimicrobial and antifungal activities. The column, Thin Layer Chromatography and the Gas Chromatography in tandem with Mass Spectrometer (GC-MS) analysis of these substances afforded five compounds namely: Hexadecanoic acid-ethyl ester, Ethyl Oleate, Hexadecanoic acid butyl ester, Octadecanoic acid butyl ester and Docosanoic acid. Antimicrobial and antifungal activities of ethyl oleate as well as the antioxidant and antimicrobial activities of Hexadecanoic acid Butyl ester had been reported in previous studies.